Changes in energy metabolism in rats during allergic dermatitis = Изменения энергетического метаболизма у крыс при аллергическом дерматите - A. I. Bereznyakova; V. F. Cheremisina; O. D. Zhemela; W. Zukow (Kazimierz Wielki University, 2016)
Bereznyakova A. I., Cheremisina V. F., Zhemela O. D., Zukow W. Changes in energy metabolism in rats during allergic dermatitis = Изменения энергетического метаболизма у крыс при аллергическом дерматите. Journal of Education, Health and Sport. 2016;6(1):251-261. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45355 http://ojs.ukw.edu.pl/index.php/johs/article/view/3362 https://pbn.nauka.gov.pl/works/710502       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016.     UDC 616.37-002-036.11 УДК 616.37-002-036.11   Changes in energy metabolism in rats during allergic dermatitis   ИЗМЕНЕНИЯ ЭНЕРГЕТИЧЕСКОГО МЕТАБОЛИЗМА У КРЫС ПРИ АЛЛЕРГИЧЕСКОМ ДЕРМАТИТЕ   A. I. Bereznyakova, V. F. Cheremisina, O. D. Zhemela, W. Zukow А. И. Березнякова, В. Ф. Черемисина, О. Д. Жемела, В. Жуков   Национальный фармацевтический университет, г. Харьков, Украина National University of Pharmacy, Kharkov, Ukraine Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Kazimierz Wielki University, Bydgoszcz, Poland   Abstract             A study is a close relationship between the functional activity of lymphocytes and their energy metabolism in allergic dermatitis. It has been shown that acute allergic dermatitis is a disease, causing sharp changes in the energy metabolism of the skin. Established a unidirectional change in the content of adenine nucleotides in blood lymphocytes and skin homogenates in rats with allergic dermatitis. However, the concentration macroergs blood lymphocytes is significantly higher than in the homogenate of the skin. Application of 0.5% dimecine ointment pathogenetically justified. It improves energy metabolism in rats of skin with atopic dermatitis, and it is expedient to recommend to the clinical trials.   Keywords: atopic dermatitis, energy metabolism, 0.5% dimecine ointment, adenosine triphosphate (ATP), adenosine diphosphate (ADP), adenosine monophosphate (AMP).   Реферат В работе изучена тесная взаимосвязь между функциональной активностью лимфоцитов и их энергетическим обменом при аллергическом дерматите. Показано, что острый аллергический дерматит, как заболевание, вызывает четкие сдвиги в энергетическом обмене кожи. Установлено однонаправленное изменение содержания адениловых нуклеотидов в лимфоцитах крови и гомогенате кожи у крыс с аллергическим дерматитом. Однако, концентрация макроэргов в лимфоцитах крови значительно выше, нежели в гомогенате кожи. Применение 0,5 % димециновой мази патогенетически обосновано. Она улучшает показатели энергетического обмена кожи у крыс с аллергическим дерматитом и ее целесообразно рекомендовать к клиническим испытаниям.   Ключевые слова: аллергический дерматит, энергетический метаболизм, 0,5 % димециновая мазь, аденозинтрифосфат (АТФ), аденозиндифосфат (АДФ), аденозинмонофосфат (АМФ).   Реферат ЗМІНИ ЕНЕРГЕТИЧНОГО МЕТАБОЛІЗМУ У ЩУРІВ ПРИ АЛЕРГІЧНОМУ ДЕРМАТИТІ. В роботі вивчено тісний взаємозв'язок між функціональною активністю лімфоцитів та їх енергетичним обміном. Показано, що гострий алергічний дерматит, як захворювання, викликає чіткі зрушення в енергетичному обміні шкіри. Встановлено односпрямована зміна вмісту аденілових нуклеотидів у лімфоцитах крові та гомогенаті шкіри у щурів з алергічним дерматитом. Однак, концентрація макроергів у лімфоцитах крові значно вище, ніж в гомогенаті шкіри. Застосування 0,5% димецинової мазі патогенетично обґрунтоване. Вона покращує показники енергетичного обміну шкіри у щурів з алергічним дерматитом і її доцільно рекомендувати до клінічних випробувань.   Ключові слова: алергічний дерматит, енергетичний метаболізм, 0,5 % димецинова мазь, аденозинтрифосфат (АТФ), аденозиндифосфат (АДФ), аденозинмонофосфат (АМФ).